TOXIC AND HYGIENIC CHARACTERISTICS OF THE COMPOUNDS OF THE BENZOFURAN SERIES WITH THE RISK ASSESSMENT FOR WORKERS’ HEALTH - Горохова, Лариса Геннадьевна (Medicine in Kuzbass, 2019)
Production of medicines is impossible without substantiation of hygienic standards that ensure the labour safety of workers when producing potentially dangerous chemical compounds. Subject of the study. The process of obtaining an antiarrhythmic drug (amiodarone) includes the synthesis of benzofuran derivatives: 2-butyrylbenzofuran (BBF), 2-butyl-3-(4-oxybenzoyl)benzofuran (BOB), 2-butyl-3-(3,5-diiodo-4-oxybenzoyl)benzofuran (IBBF). The objective of the study is the toxic and hygienic characteristics of the effects of amiodarone and intermediates for synthesis on the body with the substantiation of hygienic standards in the air of the working area. Materials and methods. A complex of toxic and hygienic studies was carried out. In the experiments, various modes (single, repeated, chronic) and methods of exposure (intragastric, inhalation, epicutaneous) were modeled. The experiments were conducted using outbred mice, CBA and C57BI mice, rats, guinea pigs, dogs and rabbits. Main results. In terms of the average lethal doses (LD50), all compounds belong to moderately hazardous substances (hazard class III) without significant differences in species and sexual sensitivity. Amiodarone does not irritate the skin and mucous membranes of the eyes, but has a moderate skin resorptive effect. The remaining compounds had a mild irritant effect on the skin and mucous membranes of the eyes, did not have a skin-resorptive effect. Biochemical analysis of blood serum revealed violations of the portal blood circulation with the addition of functional renal failure to the liver lesion, with the most marked organotoxic effect in iodine-containing benzofuran derivatives. BOB and IBBF have an average ability to cumulate, and BBF and amiodarone have a marked ability to cumulate. The thresholds for acute inhalation action (Limac) are set at the following levels: > 180 mg/m3 is for BBF; 274.8 mg/m3 is for BOB and 67.8 mg/m3 for IBBF. Amiodarone Limac is determined by the calculation method at the level of 19.8 mg/m3. The predicted value of the threshold for chronic inhalation action of amiodarone is approximately 2.4 mg/m3. Tentative safe levels of the exposure at 1 mg/m3 for 2-butyrylbenzofuran and 2-butyl-3-(4-oxybenzoyl)benzofuran and at the level of 0.3 mg/m3 for 2-butyl-3-(3,5-diiodo-4-oxybenzoyl)benzofuran were substantiated. The results of the study formed the basis for the substantiation of the maximum permissible concentration of amiodarone in the air of the working area, which was approved at the level of 0.2 mg/m3. Conclusions. Reasonable hygienic standards for the content of benzofuran derivatives in the air of the working area form the basis for the elaboration of current and preventive sanitary and epidemiological surveillance measures aimed at reducing the risk of occupationally caused and occupational diseases.